You'll never find me [large type] - Brennan, Allison (Brennan, Allison. Angelhart Investigations, 2024)
"Working alone as a private investigator is tough. Estranged from her PI family, Margo Angelhart does what she must to get by--including taking on sordid cases that pay the bills, even if she'd rather be helping those the justice system has failed. That is, until a cheating husband case she's working intersects with her siblings' corporate espionage investigation, forcing Margo to cooperate with the Angelhart firm. Now, as the siblings compare notes, it's clear they need to work together before a white-collar crime escalates to murder. With far more questions than answers and a key suspect on the run, they'll need the whole family to pitch in. But as they investigate the ever-twisting mystery, Margo isn't sharing everything. Can she learn to trust her family and heal their once-close relationship before her secrets put those she loves most in danger?"--